Nimbolide Induces Cell Apoptosis via Mediating ER Stress‐Regulated Apoptotic Signaling in Human Oral Squamous Cell Carcinoma - Peng, Bou‐Yue; Wu, Chia‐Yu; Lee, Chia‐Jung; Chang, Tsung‐Ming; Tsao, Ya‐Ting; Liu, Ju‐Fang (Environmental toxicology, 2025)
ABSTRACT Human oral squamous cell carcinoma (OSCC) poses a significant health challenge in Asia, with current therapeutic strategies failing to improve the survival rates for OSCC patients sufficiently. To elucidate the effects of Nimbolide on OSCC cell proliferation and apoptosis, we performed a series of experiments, including cell proliferation assays, annexin V/PI assays, and cell cycle analysis. We further investigated nimbolide's role in modulating endoplasmic reticulum (ER) stress, reactive oxygen species (ROS) production, and mitochondrial dysfunction using flow cytometry. Additionally, Western blotting was used to detect apoptosis‐related protein expression. Our findings reveal that nimbolide exerts its anti‐proliferative effects on OSCC cells by inducing apoptosis. The nimbolide increased intracellular ROS levels and acceleration of cellular calcium accumulation, respectively promoting endoplasmic reticulum stress and cancer cell apoptosis. Furthermore, nimbolide activates the caspase cascade by altering the mitochondrial membrane potential and apoptotic protein expression, thereby inhibiting the viability of tumor cells. Our data show that Nimbolide suppresses tumor growth through the induction of ROS production, ER stress, and mitochondrial dysfunction, resulting in apoptosis in OSCC cells. Overall, our study highlights nimbolide as a potential natural compound for OSCC therapy.